Interest-relative determination of reference for the so-called natural kind terms - Geçmen, Kerem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
The aim of the present study is to show the important role human interests/concerns play in the determination of reference for kind terms such as gold, water, tiger etc. which are commonly discussed in the literature as natural kind terms. To this end, I criticize the dominant theory of reference for these terms, namely the causal theory of reference, which holds that such terms are products of an attempt to name natural kinds, thus attributing humanity only one and universal concern with respect to the natural materials they see around them. A strong pillar for this idea is the common tendency of linguistic communities to go on using the term exclusively for things having a certain internal structure in both real and counterfactual situations. With a view to argue against this, I give some examples of real and counterfactual situations in which linguistic communities seem to have different tendencies, that is, tendencies to use the terms without taking the revealed underlying structure as the criterion determining what should or should not count as a member of the kind in question. This way, I attempt to take down the pillar supporting the causal theorists’ assumption that people named natural kinds when they used terms like gold, water or tiger. This allows me to criticize this theory for ignoring the possibility that intentions different from naming natural kinds can make communities attempt to name ordinary kinds and that we have no justification in believing that terms like gold, water, tiger etc. were coined with the intention of naming natural kinds. I try to explain how other intentions can lead to naming other kinds in different contexts by introducing the concept of “interests” and discuss them in order to illuminate the various ways in which they can influence the determination of reference for the socalled natural kind terms.
Keywords: Naturalness (Linguistics); Semantics (Philosophy)